To Achieve Carbon Neutrality Targets in Pakistan: New Insights of Information and Communication Technology and Economic Globalization - Iqbal, Kashif; Hassan, Syed Tauseef; Wang, Yichu; Shah, Muhammad Haroon; Syed, Madeeha; Khurshaid, Khurshaid (Frontiers in Environmental Science, 2022)
In recent years, information and communication technology (ICT) is used in every sphere of life, from business to services, education to culture, infrastructure to transportation, and art to entertainment. The current study aims to assess the impact of ICT, economic growth, and globalization on CO2 emission in the context of Pakistan. For empirical estimation, the current study applied an innovative methodological approach called generalized linear model (GLM) and robust least square (ROBUSTLS) technique for the years 1990–2019. The key finding of this study shows that economic growth has a positive and significant effect on CO2 emission, which confirm that economic growth accelerates the rate of CO2 emission, while the study also reveals that ICT usage (more specifically ICT-internet and ICT-mobilesubscription) has a negative but significant effect on CO2 emission, which confirms that the usage of ICT (more specifically ICT-internet and ICT-mobile subscription) does not contribute positively to CO2 emission. Furthermore, the coefficient of globalization has a positive and significant effect on the CO2 emission, which confirms that globalization accelerates the CO2 emission in the country. Also, the results indicate that ICT usage (more specifically ICT-internet and ICT-mobile subscription) could boost economic growth and mitigate climate change. Based on the policy perspective, the government of Pakistan needs to strategically focus on the ICT sector and more specifically on technological innovations to promote sustainable economic growth in the country.